From Sedentary to Success: How Physical Activity Transforms Diabetes Management: A Systematic Review - Sorina Ispas; Andreea Nelson Twakor; Nicoleta Mihaela Mindrescu; Viorel Ispas; Doina Ecaterina Tofolean; Emanuela Mercore Hutanu; Adina Petcu; Sorin Deacu; Ionut Eduard Iordache; Cristina Ioana Bica; Lucian Cristian Petcu; Florentina Gherghiceanu; et al. (Journal of Mind and Medical Sciences, 2025)
The global rise in type 2 diabetes mellitus (T2DM) calls for an urgent focus on lifestyle interventions, particularly physical activity, as a critical factor in its management and prevention. This systematic review evaluates the impact of physical activity and sedentary behavior on glycemic control in individuals with T2DM. Studies included in this review were selected based on specific criteria: randomized controlled trials involving adults aged 18 and older, published in English between January 2018 and May 2024, with full-text availability and quantifiable outcome results. Exclusion criteria included non-peer-reviewed research, small sample sizes, and studies limited to abstracts, posters, or editorials. The analysis of the selected studies revealed that regular physical activity, including aerobic exercises and resistance training, significantly improves glycemic control as measured by fasting blood glucose (FBG) and glycated hemoglobin (HbA1C) levels. Reductions in sedentary behavior were also associated with better metabolic outcomes, highlighting the importance of integrating physical activity into daily routines for individuals with T2DM. These findings feature the need for continued research to refine and optimize lifestyle interventions to mitigate the global burden of T2DM.